China [videorecording] beyond the clouds - Agland, Phil.; Noxon, Nick.; Simon, Tom.; National Geographic Society, Washington, D.C. (Washington, D.C. The Society, 1994)
Documents Lijiang, market town in Southwest China and the Chinese community - how they face economic reform, gang violence and drug abuse. Includes the way of life of the Lu family, Mr. Mu's dealing with the aftermath of his nephew's murder and the Chinese officers inquiry into the teenager's death and Dr. Tang's acupuncture treatment.
Pt.1. A small town in China/A sense of family -- Pt.2. For the sake of our children/to be remembered.
VHS.
Narrated by Lisa Lu.
Keywords: China -- Description and travel; China -- Politics and government; China -- Social life and customs